Hubungan Self-Talk dan Dukungan Sosial Terhadap Tingkat Kecemasan Menyusun Skripsi Pada Mahasiswa Keperawatan Semester Akhir Universitas Indonesia Maju Jakarta Tahun 2023 - Novie Indah Wulanndari; Saiful Gunardi; Emi Yuliza (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2024)
Final year students are required to write a thesis and usually often find various difficulties that can develop into negative feelings that cause anxiety. Some things that cause anxiety in individuals are negative experiences, lack of social support, and irrational thoughts. Anxiety can be prevented by self-talk techniques to change negative thoughts into positive ones, as well as by getting good social support. The purpose of this study was to determine the description of age, gender characteristics, self-talk, social support, and anxiety levels and to determine the relationship of self-talk to anxiety levels in students, and to determine the relationship of social support to anxiety levels in students. In this study using a quantitative approach method with a cross sectional design with a sampling technique that is a random sampling sample with a sample of 53 students at the Advanced University of Indonesia. The results of the chi-square test for the relationship of self-talk to the level of anxiety p-value is 0.005 <0.05 and the chi-square results for the relationship of social support to the level of anxiety p-value is 0.003 <0.05, so there is a relationship of self-talk to the level of anxiety in students and there is a relationship of social support to the level of anxiety in students.